War and border societies in the middle ages - Goodman, Anthony, 1936-; Tuck, Anthony (Routledge, 1992)
Examines the organisation behind societies which were 'organised for war' on a day-to-day basis. Drawing on a substantial body of Anglo-Scottish archive material the authors trace the first developed form of 'marcher' society.